Autobiography of nursing: nursing professionalization during the war - Ana Choperena Armendáriz (Universidad de Alicante, 2013)
This paper proposes an historical analysis of a group of nurses whose autobiographies of dramatic experiences in the exercise of his profession during the American Civil War helped to shape the nursing profession. The autobiographies are an important component of self-perception that not only becomes a way of conveying a reality from the subjective point of view and personal, but also helps shape a collective identity. Thus, the historical analysis of the experiences of nurses can lead to understanding of the nature of a young profession that came in the nineteenth century and that has taken shape over the twentieth century, reaching a clearly defined status and self-discipline with its development and specific practice. We have chosen the context of the American Civil War because of its impact in the professional development of nursing. It is well known that the experience of the dramatic events excites reflection after a while, and often results in retrospective autobiographical accounts that reflect the referential aspect of events.